Non-compliant Managers, Judging Citizens: An Experiment of Motives, Identities, and Public Reaction to Bureaucratic Rule Breaking. (4th March 2023) - Fleming, Casey J.; Bodkin, Candice P.
Abstract: Despite the serious demands for public organizations to maintain political accountability and bureaucratic responsiveness, rule breaking persists among employees across all levels. Unlike our deeper understanding of corruption of elected officials, myriad questions remain regarding the nature of the public response to policy violations of government bureaucrats working in politically neutral administrative positions. This study uses a survey experiment to investigate factors influencing the intensity of citizens' recommended punishments for rule-breaking local government managers, specifically testing the effects of managers' demographic attributes of age, race, and gender as well as their motivations for the violations. Findings strongly suggest that motive matters to citizens in this context, with prosocial rule-breaking managers incurring significantly less harsh penalties than destructive rule-breakers for all age-race-gender profiles. However, an absence of demographic information nullifies penalty differences between prosocial and destructive rule-breaking managers. Among the demographic attributes, only the managers' race predicted the severity of punishments favored by citizens. No interaction effects between manager attributes were present. Results suggest public communications emphasizing person and purpose are particularly important for local government managers in this context.